Effects of Programmed Local Delivery from a Micro/Nano‐Hierarchical Surface on Titanium Implant on Infection Clearance and Osteogenic Induction in an Infected Bone Defect. Issue 11 (15th April 2019) - Li, Dize; Li, Yihan; Shrestha, Annie; Wang, Si; Wu, Qingqing; Li, Lingjie; Guan, Chao; Wang, Chao; Fu, Tiwei; Liu, Wenzhao; Huang, Yuanding; Ji, Ping; et al.
Abstract: The two major causes for implant failure are postoperative infection and poor osteogenesis. Initial period of osteointegration is regulated by immunocytes and osteogenic‐related cells resulting in inflammatory response and tissue healing. The healing phase can be influenced by various environmental factors and biological cascade effect. To synthetically orchestrate bone‐promoting factors on biomaterial surface, built is a dual delivery system coated on a titanium surface (abbreviated as AH‐Sr‐AgNPs). The results show that this programmed delivery system can release Ag + and Sr 2+ in a temporal‐spatial manner to clear pathogens and activate preosteoblast differentiation partially through manipulating the polarization of macrophages. Both in vitro and in vivo assays show that AH‐Sr‐AgNPs‐modified surface renders a microenvironment adverse for bacterial survival and favorable for macrophage polarization (M2), which further promotes the differentiation of preosteoblasts. Infected New Zealand rabbit femoral metaphysis defect model is used to confirm the osteogenic property of AH‐Sr‐AgNPs implants through micro‐CT, histological, and histomorphometric analyses. These findings demonstrate that the programmed surface with dual delivery of Sr 2+ and Ag + has the potential of achieving an enhanced osteogenic outcome through favorable immunoregulation. Abstract : Initial period of bone healing goes through several stages, which is influenced by various environmental factors. The silver nanoparticle and strontium–introduced hierarchical structure on porous Ti implant surface controls Ag + and Sr 2+ release and advantageously provides micro/nano surface topography. This multifunctional local delivery system orchestrates several bone healing stages by killing bacteria, regulating macrophage polarization, and stimulating osteoblast differentiation.